Applications of Calorimetry in a Wide Context Differential Scanning Calorimetry, Isothermal Titration Calorimetry and Microcalorimetry - Ali Elkordy, Amal (IntechOpen, 2013)
Calorimetry, as a technique for thermal analysis, has a wide range of applications which are not only limited to studying the thermal characterisation (e.g. melting temperature, denaturation temperature and enthalpy change) of small and large drug molecules, but are also extended to characterisation of fuel, metals and oils. Differential Scanning Calorimetry is used to study the thermal behaviours of drug molecules and excipients by measuring the differential heat flow needed to maintain the temperature difference between the sample and reference cells equal to zero upon heating at a controlled programmed rate. Microcalorimetry is used to study the thermal transition and folding of biological macromolecules in dilute solutions. Microcalorimetry is applied in formulation and stabilisation of therapeutic proteins. This book presents research from all over the world on the applications of calorimetry on both solid and liquid states of materials.